2016
DOI: 10.1016/j.dental.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Glycine: A potential coupling agent to bond to helium plasma treated PEEK?

Abstract: OBJECTIVES To test the tensile bond strength (TBS) between two self-adhesive resin composite cements and PEEK after helium plasma treatment and used glycine as a potential coupling agent incorporated in different adhesives. METHODS In summary, 896 air-abraded PEEK specimens were fabricated. Half of the specimens were treated with cold active inert helium plasma and the other half were left non-treated. Both groups were then split in two groups: In group 1 (n=256), 64 specimens were pre-treated with: (a) soft-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Traditionally, sandblasting and chemical etching are applied for surface treatment of different PEEK materials [6,7,8,9]. The utilization of plasma as an innovative approach to treating PEEK surfaces prior to bonding has also been used and has resulted in widely diverse results [10,11,12,13,14]. For instance, the studies of Stawarczyk et al and Schmidlin et al revealed no positive influence of helium plasma on the shear and tensile bond strength of ceramic-filled PEEK to two self-adhesive resin cements [12,15], whereas in the study of Zhou et al, the utilization of argon plasma improved the bond strength of PEEK to the tested resin cement and veneering composite [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, sandblasting and chemical etching are applied for surface treatment of different PEEK materials [6,7,8,9]. The utilization of plasma as an innovative approach to treating PEEK surfaces prior to bonding has also been used and has resulted in widely diverse results [10,11,12,13,14]. For instance, the studies of Stawarczyk et al and Schmidlin et al revealed no positive influence of helium plasma on the shear and tensile bond strength of ceramic-filled PEEK to two self-adhesive resin cements [12,15], whereas in the study of Zhou et al, the utilization of argon plasma improved the bond strength of PEEK to the tested resin cement and veneering composite [11].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of plasma as an innovative approach to treating PEEK surfaces prior to bonding has also been used and has resulted in widely diverse results [10,11,12,13,14]. For instance, the studies of Stawarczyk et al and Schmidlin et al revealed no positive influence of helium plasma on the shear and tensile bond strength of ceramic-filled PEEK to two self-adhesive resin cements [12,15], whereas in the study of Zhou et al, the utilization of argon plasma improved the bond strength of PEEK to the tested resin cement and veneering composite [11]. Schwitalla et al explored the influence of a cold, low pressure plasma mixture of argon/oxygen gases on the shear bond strength of three types of PEEK (unfilled PEEK, ceramic-filled PEEK, and pigment powder-filled PEEK) to veneering composite and observed insignificant improvement of the bond strength after combining sandblasting with plasma treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the adhesion properties, the present investigation also focused on the bond strength between the UAKP and denture resin, which has historically been challenging due to the characteristic inert surface character of highperformance thermoplastics 22) . Even though current scientific evidence has thoroughly dealt with bonding characteristics between high-performance thermoplastics to polymer-based materials like veneering resins [23][24][25][26][27][28] and resin composite [29][30][31][32][33][34][35][36][37][38][39][40][41][42] , data on the bonding behavior to denture resin is truly scarce 37) . The most important findings are that a surface pretreatment combined with appropriate specific conditioning step is necessary to realize a sufficient bonding to dental composites.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated whether different surface pretreatments can improve the bond strength between PEEK and dental materials [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . In those studies, the PEEK surface was pretreated by sandblasting with piranha solution 17,18,21,23,24,31) , sulfuric acid 17,18,21,23,24,30) , or with different types of plasma 20,26,29) . In addition, the application of various adhesive systems after pretreatment have been investigated 17,[20][21][22][23][24]26,31,32) .…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, the PEEK surface was pretreated by sandblasting with piranha solution 17,18,21,23,24,31) , sulfuric acid 17,18,21,23,24,30) , or with different types of plasma 20,26,29) . In addition, the application of various adhesive systems after pretreatment have been investigated 17,[20][21][22][23][24]26,31,32) . Those studies reported that the use of adhesive systems based on methyl methacrylate monomer as the main component yields a higher bond strength between the PEEK and dental materials.…”
Section: Introductionmentioning
confidence: 99%